Management of an Isolated Type I Ankyloblepharon Filiforme Adnatum (AFA) with Coloboma of the Upper Eyelid in a Newborn - Mayangsari, Dian; Doemilah, Ratna (Vision Science and Eye Health Journal, 2023)
Introduction: Ankyloblepharon filiforme adnatum (AFA) is a rare congenital condition marked by one or more bands of tissue adhering partially or entirely to the ciliary margins of the upper and lower eyelids at the gray line. This case study illustrates the ease of treating the condition. A general ophthalmologist could do that. Case Presentation: A one-month-old infant was admitted to the outpatient clinic. Since birth, he could not open his eyes due to upper and lower eyelid adhesions. There was also a coloboma in the one-third lateral upper eyelid in the right eye. The evaluation of other body systems was normal. The infant was diagnosed with type I AFA and underwent surgery under general anesthesia. After crushing the band with the clamp, the bands of tissue were excised with the blade. The coloboma was reconstructed by applying primary closure and pentagonal shape incision, then sutured with 8-0 vicryl. The eyelids were separated with an aligned lid margin. Conclusions: Simple surgical procedures are used to treat congenital ankyloblepharon. It depends on the nature and extent of the adhesions along the lid margin. To reduce the risk of amblyopia, early treatment should be initiated immediately.